2D Perovskite‐Based Self‐Aligned Lateral Heterostructure Photodetectors Utilizing Vapor Deposition. Issue 3 (4th December 2018) - Hwang, Bohee; Lee, Jang‐Sik
Abstract: 2D organic–inorganic hybrid perovskites (OIPs) hold great promise for electronics and optoelectronics due to structural diversity, high photoluminescence, and tunable bandgap. Moreover, integrating 2D OIPs with the 2D materials including graphene, transition metal dichalcogenide, and other OIPs gives opportunities for various options in constructing new types of heterojunctions with novel functionalities such as enhanced charge transport properties or chemical stability. Here, a sequential vapor deposition method is presented to fabricate 2D OIP lateral heterostructure films (C4 H9 NH3 )2 PbI4 (BA2 PbI4 )–(C4 H9 NH3 )2 (CH3 NH3 )Pb2 I7 (BA2 MAPb2 I7 ) for photodetector applications. The lateral heterostructure is realized using thermal evaporation to deposit lead iodide (PbI2 ) films, then exploiting vapor transport of organic vapor to form BA2 PbI4, BA2 MAPb2 I7, and self‐aligned lateral heterostructure. A photodetector based on the lateral structure (BA2 PbI4 –BA2 MAPb2 I7 ) shows larger photocurrent and higher on/off ratio (>10 2 ) than those of single material‐based devices (BA2 PbI4, BA2 MAPb2 I7 ). This method to fabricate 2D OIP lateral heterostructure suggests a simple way to synthesize 2D perovskite heterostructure and may open the possibility of 2D OIP perovskites to be integrated in emerging optoelectronic devices. Abstract : A self‐aligned lateral heterostructure BA2 PbI4 –BA2 MAPb2 I7 (BA = C4 H9 NH3 ; MA = CH3 NH3 ) are demonstrated by using sequential vapor deposition. Photodetectors based on the lateral heterostructure show better optoelectronic performances than those of single material‐based devices (BA2 PbI4 or BA2 MAPb2 I7 ). The proposed method to fabricate the lateral heterostructure has good prospects to be used for advanced optoelectronic devices.